2022
DOI: 10.1088/1741-2552/ac88f6
|View full text |Cite
|
Sign up to set email alerts
|

EEG microstate in first-episode drug-naive adolescents with depression

Abstract: Background: A growing number of studies have revealed significant abnormalities in EEG microstate in patients with depression, but these findings may be affected by medication. Therefore, how the EEG microstates abnormally change in patients with depression in the early stage and without the influence of medication has not been investigated so far. Methods: Resting-state EEG data and Hamilton Depression Rating Scale (HDRS) were collected from 34 first-episode drug-naïve adolescent with depression and 34 matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 42 publications
2
9
2
Order By: Relevance
“…Different views exist regarding the characteristics of the changes in microstate A. For instance, according to Zhao et al, patients with depression exhibit a decrease in the occurrence and coverage of microstate A in their EEG characteristics [39]. In the current research, there was a negative correlation found between microstate C-to-A transition and the anxiety and depression levels in patients.…”
Section: Discussionsupporting
confidence: 42%
“…Different views exist regarding the characteristics of the changes in microstate A. For instance, according to Zhao et al, patients with depression exhibit a decrease in the occurrence and coverage of microstate A in their EEG characteristics [39]. In the current research, there was a negative correlation found between microstate C-to-A transition and the anxiety and depression levels in patients.…”
Section: Discussionsupporting
confidence: 42%
“…LZ complexity is known to be a robust marker of brain dysfunction, both when computed at the signal level (e.g. in depression ( Bachmann et al, 2015 ), schizophrenia ( Ibáñez-Molina et al, 2018 ) and epilepsy ( Abásolo et al, 2007 , Bai et al, 2015 )) and at microstates level (for example ( Artoni et al, 2022 , Tait et al, 2020 , Zhao et al, 2022 )).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the biological significance of LZC may differ from that indicated by other microstate indicators [34]. For instance, in other studies, MSLZC was found to be higher in patients with depression than in controls [35], and LZC in patients with thalamic ischemic stroke has been found to be higher compared to the controls [36].…”
Section: Discussionmentioning
confidence: 86%